A taxonomic review of the genus Neptosternus Sharp of China with the description of a new species (Coleoptera: Dytiscidae: Laccophilinae) - Zhao, Shuang; Hájek, Jiří; Jia, Fenglong; Pang, Hong (Zootaxa, 2012)
Chinese species of Neptosternus Sharp, 1882 are reviewed. Neptosternus punctatus sp. nov. from Guangdong is describedand illustrated. Neptosternus yanbini Bian & Ji, 2009, described from Hainan, is shown to be a junior subjective synonymof the widely distributed Oriental Neptosternus hydaticoides (Régimbart, 1877) (syn. nov.). Neptosternus strnadi Hendrich& Balke, 1997 and N. maculatus Hendrich & Balke, 1997 are recorded from China for the first time. Anotherspecies—Neptosternus wewalkai Balke, Hendrich & Yang, 1997, known previously only from a single female from northernVietnam—is re-described based on male and female specimens from Guangxi, and also recorded from China for the firsttime. Neptosternus pocsi Satô, 1972 is removed from the Chinese fauna. A key to the six Neptosternus occurring in mainland China is presented.